PERFORMANCE OF BROILER CHICKEN FED DIFFERENT LEVELS THYME, ADIANTUM, ROSEMARY AND THEIR COMBINATION - & et al., TAYEB (IRAQI JOURNAL OF AGRICULTURAL SCIENCES, 2019)
The objective of this study was to investigate the effects of different levels of medical plants (thymus vulgaris, Adiantum capillus-veneris L, Rosemarinus officinalis and their combination) supplemented in the diet on Physiological and Growth performance traits of broiler chicken. T1 Control (no supplemented), T2 Thyme powder 5 g/kg, T3 Thyme powder 10 g/kg, T4 Adiantum powder 3 g/kg, T5 Adiantum powder 5 g/kg, T6 Rosemary powder 5 g/kg, T7 Rosemary powder 10 g/kg and T8 Mixture (Thyme , Adiantum and Rosemary) with 7.5 g/kg +4 g/kg and 7.5 g/kg, respectively. A Total of 288 unsexed broiler chicks, were randomly distributed to eight treatments with three replicate. Medical plants at different levels added to basal diets at 7th days old. Live body weight and mortality rates were measured weekly. At the end of the experiment the following traits were measured: carcass traits, hematology, blood biochemical, hormonal responses, and serum enzymes parameters. There is a significant effect of medicinal plants on live body weight, feed intake and dressing percentage. Mortality rate in T2 and T7 was significant highest. While, feed conservation was not influenced by medicinal plants. There was a significant effect of treatments on abdominal fat and liver weights. Adiantum powder at different levels has significant effect on bursa and spleen weights compared to other groups. There was a significant effect of treatments on albumin, globulin, cholesterol and glucose concentration. Medicinal plants significantly affect hormonal response. The combination of plants (T8) investigated high concentration of T3 and T4 hormones. Also, addition of rosemary observed higher concentration of TSH and GH hormones. There was significant effect of medical plants on AST and ALT enzymes. There is none significant effect of medical plants on meat color among treatment.